An essay on Hardy - Bayley, John (Cambridge, New York: Cambridge University Press, 1978)
This 1981 book suggests an insightful approach to Hardy as a poet and novelist. With the novels in particular it concentrates not so much on ideas and attitudes as on the texture of the writing, and on the crucial importance in it between one kind of exposition and another.